Efficient Energy Transfer and Singlet Fission in Co‐Deposited Thin Films of Pentacene and Anthradithiophene - Nico Hofeditz; Julian Hausch; Katharina Broch; Wolfram Heimbrodt; Frank Schreiber; Marina Gerhard (Advanced Materials Interfaces, 2024)
Abstract Co‐deposited molecular heterostructures with statistical intermixing of the constituents are attractive candidates to tune the optical and the transport properties, as well as the ability to promote photophysical processes like singlet fission. In order to comprehend and control the singlet fission mechanism in these systems, it is of utmost interest to study the underlying excited state dynamics. In this work, thin films of anthradithiophene blended with the efficient singlet fission material pentacene are investigated by means of time‐resolved and temperature‐dependent photoluminescence spectroscopy with a time resolution of a few picoseconds. The analysis of the photoluminescence dynamics points toward efficient funneling of excitons from anthradithiophene via isolated pentacene molecules to agglomerates of pentacene, where eventually singlet fission occurs. The efficient and largely temperature‐independent quenching of the luminescence in anthradithiophene is attributed to a favorable cascade‐like alignment of the energy levels, and it is hypothesized that Förster resonance energy transfer is the main driving mechanism for exciton transport to pentacene agglomerates. The system investigated here can serve as a blueprint for the design of other molecular heterostructures with spatially separated light harvesting and singlet fission regions.